Significant Geogenic and Anthropogenic Factors Concerning Contamination of Groundwater Resources in Afghanistan - Hayat, Ehsanullah; Baba, Alper; Baba, Alper (Nevşehir Hacı Bektaş Veli Üniversitesi, 2017)
In recent years, the groundwater quality in Afghanistan has raised some concerns as far as very few studies exist about its quality. The main reason behind the little knowledge about groundwater quality is that the country is recovering from decades of war and instability. Being one of the main and reliable sources for drinking, public and private institutions have started some initial investigations from the last few years to examine groundwater quality through the entire country. Still, it will take some time to complete such a broad study. In this article, an extensive review of the literature about the groundwater quality of Afghanistan is conducted where the existing raw data is analyzed as well to obtain some important results and indicate them scientifically.
2nd International Conference on Civil and Environmental Engineering (ICOCEE), CAPPADOCIA, May 8 - 10, 2017, Nevsehir
Keywords: Arsenic; Groundwater quality; Geogenic factors; Afghanistan